Risk factors and mediation role of sleep quality for depression in cognitively frail older adults: a cross-sectional study - Xiaoxing Lai; Yonghua Cai; Hongwei Zhu; Zhiyuan Zhang; Xinyue Zhang; Yang Li; Jiazhen Liu; Xiaopeng Huo (Frontiers in Aging Neuroscience)
ObjectiveAimed to investigate the risk factors associated with depression in community-dwelling older adults with cognitive frailty and to examine the mediating role of sleep quality in the relationship between activities of daily living (ADL) and depression.MethodsA cross-sectional study was conducted using convenience sampling, enrolling older adults with cognitive frailty from six communities in Beijing from July 2023 to December 2023. Cognitive frailty was assessed using the Montreal Cognitive Assessment (MoCA) alongside with the Fried Frailty Phenotype, while depressive symptoms were measured with the Geriatric Depression Scale (GDS-15). Multivariate logistic regression analysis was used to identify risk factors influencing depression, and mediation analysis was employed to explore the mediating effect of sleep quality on the relationship between ADL and depression.ResultsAmong the 529 elderly participants with cognitive frailty, 128 (24.2%) were found to exhibit depressive symptoms. Multivariate logistic regression identified ADL [Mild Dependence: OR = 176.729 (95% CI 32.427–963.172), p < 0.001; Moderate Dependence: OR = 51.769 (95% CI 12.541–213.697), p < 0.001], loneliness [OR = 13.821 (95% CI 6.095–31.338), p < 0.001], and sleep quality [Suspected Insomnia: OR = 7.310 (95% CI 2.316–23.074), p = 0.001] were significantly associated with depression. Sleep quality was found to mediate the relationship between ADL and depression, accounting for 2.82% of the total effect.ConclusionDependence in ADL, loneliness, and poor sleep quality are potential risk factors of depression for cognitive frailty in aging adults. Moreover, sleep quality was found to mediate the relationship between ADL dependence and depressive symptoms.